PELATIHAN PENYELENGGARAAN FARDHU KIFAYAH BAGI TOKOH MASYARAKAT DESA KAMPUNG MINAS TIMUR KECAMATAN MINAS KABUPATEN SIAK - Rahman, Rahman (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This article is the result of community service regarding the implementation of fardhu kifayah for community leaders in Kampung Minas Timur Village, Minas District, Siak Regency with the problem of a lack of public understanding of the implementation of fardhu kifayah so that training is needed. The training for the implementation of fardhu kifayah was attended by several community leaders who were sent based on the recommendation of the village head. This training method is divided into two categories, namely the presentation of the material and continued with the practice of how to bathe, shroud, pray and bury the body. The result is that after holding training activities for organizing fardhu kifayah, they already have the knowledge to carry out fardhu kifayah and are ready to practice it if a fellow Muslim dies.